HUBUNGAN POLA MAKAN DENGAN KEJADIAN HIPERTENSI PADA USIA DEWASA PERTENGAHAN (MIDDLE AGE) - Achmad Sya'id; Hella Meldy Tursina (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Food is very important to influence a person's nutrition. Applying a healthy diet in everyday life is very important in maintaining the body to avoid various diseases. The application of a healthy diet such as not consuming foods that contain high sodium and fatty foods in a long period of time or done repeatedly. Diet is one of the major modifiable risk factors for hypertension. Tempeh Health Center has the highest hypertension patients in Lumajang Regency. The purpose of this study was to determine the relationship between diet and the incidence of hypertension in middle age at Tempeh Health Center. Method: this research is a quantitative research that is correlation by using cross sectional design. The population used is middle-aged adults, both men and women aged 45-59 years who seek treatment at the Tempeh Health Center with visits during the last 3 months, which is 270 population. The sample in this study amounted to 161 respondents. The results of the study: diet with a bad category as many as 117 people (72.7%). while respondents who experience hypertension as many as 89 people (55.3%). Analysis: using the spearman rank test, a p-value of 0.001 < 0.05 was obtained, which means that there is a strength of the coefficient relationship with a value of 0.345, a moderate correlation between diet and the incidence of hypertension in middle age at the Tempeh Health Center in 2022. Discussion: diet has a very important role that can cause hypertension. Increasingly frequent consumption of foods high in sodium and fatty foods in large portions and in repeated meals over a long period of time can cause hypertension. It is expected that health workers provide counseling or health promotion about healthy eating for hypertensive patients.